2005
DOI: 10.1093/brain/awh486
|View full text |Cite
|
Sign up to set email alerts
|

Short-lived plasma blasts are the main B cell effector subset during the course of multiple sclerosis

Abstract: Multiple sclerosis is a chronic inflammatory and demyelinating disorder of the CNS with an unknown aetiology. Although intrathecal immunoglobulin G (IgG) synthesis is a key feature of the disease, little is still known about the B cell response in the CNS of multiple sclerosis patients. We analysed the phenotype and kinetics of different B cell subsets in patients with multiple sclerosis, infectious disease (IND) and non-inflammatory neurological disease (NIND). B cells were detected in the CSF of multiple scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
212
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(238 citation statements)
references
References 42 publications
24
212
1
1
Order By: Relevance
“…Further characterization of the IgG1 ASCs in the CSF of MS patients showed that these cells express CD38, CD138, and HLA‐DR, together with dim levels of CD19 and high levels of CD27. This is in line with the results of a previous study characterizing intrathecal B cells,15 but contrasts another study that demonstrated increased numbers of CD19 – CD138 + plasma cells 16. Importantly, we show for the first time that the intrathecal IgG1 ASCs express high levels of Ki‐67, suggesting that the cells are newly derived and proliferate intrathecally.…”
Section: Discussionsupporting
confidence: 91%
“…Further characterization of the IgG1 ASCs in the CSF of MS patients showed that these cells express CD38, CD138, and HLA‐DR, together with dim levels of CD19 and high levels of CD27. This is in line with the results of a previous study characterizing intrathecal B cells,15 but contrasts another study that demonstrated increased numbers of CD19 – CD138 + plasma cells 16. Importantly, we show for the first time that the intrathecal IgG1 ASCs express high levels of Ki‐67, suggesting that the cells are newly derived and proliferate intrathecally.…”
Section: Discussionsupporting
confidence: 91%
“…Increased numbers of T cells and B cells are found in the CSF of patients with CNS infections or multiple sclerosis [3,16].…”
Section: Neuroimmune Function Of the Choroid Plexuses In Neurologicalmentioning
confidence: 99%
“…An important question is whether B cell stimulation only takes place outside the CNS, or if it also occurs intrathecally. The latter possibility is now supported by converging evidence: i) all B cell subsets, including centroblasts typical of secondary lymphoid organs, are present in the CSF of MS patients [236], ii) Short-lived plasma blasts are common in the CSF and their number correlates with intrathecal IgG synthesis, whereas long-lived plasma cells which are independent of antigen stimulation are very rare [237], iii) sequence analysis of transcribed V genes in single sorted CSF cells has identified the same clonal populations in plasma blasts and plasma cells, suggesting ongoing development of antibody secreting cells [238], and iv) ectopic germinal centers are present in the meninges of some patients with secondary progressive MS [239,240].…”
Section: Bcr/immunoglobulin V Genesmentioning
confidence: 96%